Administrative law governing the activities of law enforcement agencies under Martial Law - Holodnyk, Yurii; Savranchuk, Liudmyla; Voznyk, Mikhail; Horbach-Kudria, Ivanna; Kuzyk, Viacheslav (Universidad Hemisferios, 2024)
Effective and timely performance of duties by law enforcement officers under martial law is an important step on the way to restoring law and order disturbed by the armed conflict. The aim of the study was to analyze the structure of the mechanism of administrative law governing the activities of law enforcement agencies under martial law. The multiple-aspect research object determined the use of a wide range of methods, such as the comparative analysis and the method of comparative law. In this sense, implementing measures by the police to provide a technical forensic examination of the scene upon the discovery of suspicious explosive devices and ammunition is considered effective for ensuring law and order during martial law. During an armed conflict, the law enforcement officers carry out their activities in compliance with the provisions of administrative law governing law enforcement activities under martial law. A coordinated structure of law enforcement agencies during martial law helps to establish law and order and observe human rights and freedom. Further research on the activities of law enforcement agencies under martial law may focus on developing practical recommendations regarding the effectiveness of police activities, and these may be demining the territory and inspecting the scene by the police in the event of the discovery of explosive devices.